Netiqueta como competencia docente en la Unidad Educativa Fiscomisional La Dolorosa durante el año lectivo 2021-2022 - Ortiz León-, Erguin Joel (2024)
Currently, teachers must have digital skills defined as the set of knowledge, skills, attitudes and strategies to make critical and safe use of information society technologies, among them are netiquette skills that are standards of behavior that allow harmonic environments in network communication. The purpose of this research work is to analyze the competence of netiquette in the teachers of the Unidad Educativa Fiscomisional La Dolorosa in the 2021-2022 school year, the methodology that was applied part of the deductive method, with a quantitative approach and descriptive-exploratory type. , a research instrument was carried out for data collection based on the Common Framework for Digital Teaching Competence (2017), applied to the specific sample through the survey technique whose degree of measurement corresponds to a dichotomous scale. The results obtained show that the teachers of the educational institution are mostly located at the basic level in the netiquette competition, with which it can be argued that they know the basic rules of access and behavior in social networks, of the communication in media and digital channels, in addition to being aware of the dangers and inappropriate behaviors on the Internet that can affect their students and the need for educational prevention. Keywords: Teaching competence, Norms, Conduct, Netiquette